Pengaruh Green Place Dan Green Promotion Terhadap Keputusan Pembelian Produk Wikstea Pada Mahasiswa Fakultas Kehutanan Universitas Sumatera Utara: Pengaruh Green Place Dan Green Promotion Terhadap Keputusan Pembelian Produk Wikstea Pada Mahasiswa Fakultas Kehutanan Universitas Sumatera Utara - Pandiangan, Paulus; Hasman, Haryaji Catur Putera; Batubara, Ridwanti; Siregar, Dahrul (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2024)
This research aims: (1) To determine the influence of green places on purchasing decisions for Wikstea products among students at the Faculty of Forestry, University of North Sumatra. (2) To determine the effect of green promotion on purchasing decisions for Wikstea products among students at the Faculty of Forestry, University of North Sumatra. This research method This type of research is quantitative research and is associative in nature. The results of this research; (1) From the green place statement, in the future the procurement of Wikstea stands/outlets can be further increased to reach new consumers. (2) green promotion statement, it is hoped that the Wikstea company can make advertisements or promotions about the importance of using products that are friendly to living creatures and the environment. Keywords: Influence, Green Place, Green Promotion.